Spiritual leadership development: an exemplar protocol - Chappell, Stacie F. (Journal of management, spirituality & religion, 2020)
The nexus of spirituality and leadership infuses many leadership theories. However, there is a gap in our understanding regarding how organizations integrate spirituality with leadership development. This article makes a significant contribution to understanding the intersection of spirituality and leadership development by examining a specific facilitation protocol. It is a natural bookend to the seminal article titled "Spirituality for Business Leadership: Reporting on a pilot course for MBA's and CEO's" in which André shared his first attempt at such work. In contrast, the protocol discussed in this article has been refined by André's continued leadership and practice in this area. As well, this protocol was designed and implemented as a formal leadership development initiative within an organization. In this paper, we begin with a literature review on spiritual leadership development: the intersection of spirituality, leadership and learning; the primacy of contemplative practice; and the importance of structure. Second, we describe a leadership development program design that explicitly integrates spirituality. Finally, we discuss the implications of this protocol for future practice and research on spiritual leadership development.